1999
DOI: 10.1210/endo.140.11.7114
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Regulates the Extracellular Organization of Laminin on Astrocytes1

Abstract: Astrocytes produce laminin, a key extracellular matrix guidance molecule in the developing brain. Laminin is bound to transmembrane receptors on the surface of astrocytes known as integrins, which are, in turn, bound to the microfilament meshwork inside the astrocyte. Previous studies have shown that T4 regulates the pattern of integrin distribution in astrocytes by modulating the organization of the microfilaments. In this study, the effect of thyroid hormone on the secretion and topology of laminin in astroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(4 citation statements)
references
References 48 publications
0
3
1
Order By: Relevance
“…Our data contrast with those obtained from Farwell and Dubord-Tomasetti (29), who demonstrated that T4 but not T3 increases laminin expression. We believe, however, that this apparent discrepancy between these two works most likely reflect fundamental differences in the technical approaches such as hormone treatment schedule, hormone concentration, and differences in culture conditions.…”
Section: Egf⁄mapk-pi3k Pathways Effects On Neuritogenesiscontrasting
confidence: 99%
“…Our data contrast with those obtained from Farwell and Dubord-Tomasetti (29), who demonstrated that T4 but not T3 increases laminin expression. We believe, however, that this apparent discrepancy between these two works most likely reflect fundamental differences in the technical approaches such as hormone treatment schedule, hormone concentration, and differences in culture conditions.…”
Section: Egf⁄mapk-pi3k Pathways Effects On Neuritogenesiscontrasting
confidence: 99%
“…The role of thyroid hormones (THs), T3 and thyroxine (T4), in the development and metabolism of many tissues and organs, both in early and adult life, is mainly mediated through T3, which regulates gene expression by binding to the TH receptors (TR)-α and -β [ 47 , 48 , 49 , 50 ]. Thyroid hormones have been reported to modulate cells morphology, differentiation, and proliferation, and to regulate ECM organization and synthesis also in tendon tissue [ 17 , 18 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormone is required early in pregnancy for normal neurogenesis, neuronal migration, neuronal and glial cell differentiation, myelination, and synaptogenesis (Bernal, 2017;Eayrs, 1953;Lavado-Autric et al, 2003). In fact, thyroid hormones were shown to modify expression of genes associated with cell cycle and intracellular signaling (E2F1, p53, cyclins, and cyclin-dependent kinase inhibitors), cytoskeleton organization (actin and microtubule polymerization), and extracellular matrix contents (laminin, fibronectin, and several adhesion molecules), which are involved in neurogenesis and neuronal migration (Bernal, 2017;Farwell & Dubord-Tomasetti, 1999;Iglesias et al, 1996;Koibuchi, Jingu, Iwasaki, & Chin, 2003;Leonard & Farwell, 1997;Lin et al, 2004;). Neurogenin 2 and Reelin are also proteins involved in neuron development and neuronal migration which expression has also been proven to be modulated by thyroid hormones (Dong et al, 2009;Pathak, Sinha, Mohan, Mitra, & Godbole, 2011).…”
Section: Thyroid Hormone Axis: Ontogeny Metabolism and Molecular mentioning
confidence: 99%